Floristic patterns and disturbance history in karri forest, south-western Australia 1. Environment and species richness - Wardell-Johnson, Grant; Williams, Matthew; Mellican, A.; Annells, A. (Elsevier, 2004)
We examined the influence of disturbance history on interactions between floristic composition and environmental factors in a single community type in karri forest (site type 10, after [For. Ecol. Manage. 32 (1990) 135]) in south-western Australia. The relationship of six disturbance and site-based environmental variables, and three plant species richness variables (native, introduced and total vascular plant species) were compared using numerical taxonomic, regression and correlation approaches. Disturbance and site variables were highly intercorrelated, limiting the opportunity to directly attribute causes to observed floristic patterns. Nevertheless, management practices in karri forest are based on interrelated disturbances (e.g. high intensity slash burns were used to initiate regeneration for timber production), limiting the necessity to separate effects. Community types in karri forest have both, low a diversity (quadrat-based species richness) and species richness of the community in comparison with neighboring vegetation types. For community type 10, a diversity was negatively correlated with time-since-fire (P <0.002) and time-since-regeneration (P <0.004), but was lowest at intermediate times since disturbance (11-20 years).Although, ordination revealed no discernable pattern of sites based on floristic composition, four plant assemblages defined a priori according to time-since-disturbance were significantly different from one another (P < 0.01 by ANOSIM). Time-since-fire (and other disturbance) influenced floristic composition more than the number of recent past fires in contrast to the more species-rich, but drier and nutrient-poor neighboring jarrah forest communities where the number of past fires is more influential. Under the current climatic regime, karri forest communities are likely to undergo less long-term change in floristic patterns following disturbance than neighboring vegetation types. This is primarily because of the greater intervals between disturbance events, the few transformer weeds in the area and the rapid recovery of native plant cover following disturbance. This study has demonstrated the resilience of karri forest to various discrete disturbances currently associated with these environments, although more profound changes are likely following continuing disturbance intervention such as clearing and grazing.